Postfeminist Healthism: Understanding the Gendering of Healthism Using Menstrual Tracking Apps as an Example - Riley S; Evans A; Robson M (John Wiley and Sons Ltd on behalf of Foundation for the Sociology of Health & Illness., 2025)
‘Postfeminist healthism’ offers an essential framework for understanding how healthism is gendered. In this article, we describe and advance the concept of postfeminist sensibility and its synergistic alignments with healthism. We then consider how postfeminist healthism operates as a subjectifying force for the millions of girls, women, and other feminine-identified people globally—even when it harms their mental or physical health. We use menstrual tracking apps (MTAs) as an indicative example to both demonstrate how a postfeminist healthism acts at the intersections of bodies, subjectivity, and health, and to show the value of a postfeminist healthism in understanding MTAs. Overall, we show the importance of understanding the distinct ways in which healthism is gendered through postfeminism.
Keywords: gender; healthism; menstrual tracking apps; postfeminist healthism; postfeminist sensibility